Nitrogen Gas Partial Pressure Control Effects on Titanium Nitride Coating’s Thickness and Colour over Tungsten Carbide Substrate using PVD - Hashim, Hanizam; Md Nizam, Abd Rahman; Noraiham, Mohamad; Hassan, Attan; Mohd Soufhwee, Abd Rahman (2012)
Titanium nitride is preferred thin coating material in the industry due to its good mechanical properties and great gold color film over machining tools and decorative parts, respectively. Optimization of titanium nitride (TiN) thin film coating on tungsten carbide (WC) substrate using physical vapor deposition (PVD) process at nitrogen (N2) and argon (Ar) gases partial pressures ratio is still lacking. In this paper, relationship between partial pressure of N2 and coating thickness was investigated. Coating characterizations were carried out using a surface stylus-based profiler and a digital 800k USB 2.0 CCD DCAM and VIS version7 software with 50% contrast and brightness settings for thickness and color, respectively. The relationship between partial pressure and coating thickness was analyzed using a statistical software Minitab version 16. Higher TiN coating thickness and better gold color appearance obtained at lower N2/Argon partial pressure ratio of 0.12 compared to 0.26. The polynomial regression equation of its relationship showed a high confident level of more than 95% and P value of 0.011. The results showed good agreement with previous works. It can be used as an indicator to determine the optimum partial pressure and indirectly represent the coating quality.